Multicomponent reactions : synthesis of bioactive heterocycles - Ameta, K. L.; Dandia, Anshu (CRC Press, 2017)
"This timely book provides a succinct summary of methods for the synthesis of bioactive heterocycles using a multicomponent reaction (MCR) approach. The majority of pharmaceuticals and biologically active agrochemicals are heterocycles while countless additives and modifiers used in industrial applications are heterocyclic in nature. With the recent introduction of high-throughput biological evaluation, the importance of MCRs for drug discovery has been recognized and considerable efforts have been focused especially on the design and development of multi-component procedures for the generation of various bioactive heterocycles due to their significant therapeutic potential."- Resumé vydavatel
Keywords: heterogenní katalýza; heterocyklické sloučeniny; chemické syntézy; biologicky aktivní látky; heterogeneous catalysis; heterocyclic compounds; synthesis; bioactive compounds; elektronické knihy; sborníky; electronic books; papers of several authors